Piety and Eschatology in Early Kharijite Poetry - Donner, Fred M. (في محراب المعرفة: دراسات مهداة إلى إحسان عباس, 1997)
Don de l'auteur
Keywords: poésie kharijite

The limitations of Qur’ānic usage in early Arabic poetry: the example of a Khārijite poem - Qāḍī, Wadād al- (Festschrift Ewald Wagner zum 65. Geburtstag. 2: Studien zur arabischen Dichtung, 1994)
On a poem (a translation is given), a Rā’iyya, by the Khārijite poet ʿAmr b. al-Ḥusayn al-ʿAnbarī (d. after 130/749), composed on the occasion of a battle in Wādī ‘l-Qurā near Mecca, 130/748, in which the Khārijites were routed by an Umayyad army, and in which their leaders, including Abū Ḥamza al-Shārī (Abū Ḥamza al-Mukhtār b. ʿAwf), were killed. See Higgins 2015, who treats the same poem.
Keywords: Abū Ḥamza al-Mukhtār b. ʿAwf; poésie kharijite